EFEKTIFITAS METODE GROUP FIELD TOUR MELALUI TEKNIK SIMFONI OTAK DALAM PEMBELAJARAN PENULISAN SASTRA KREATIF - Akhmad Fauzan (Khazanah Pendidikan, 2014)
Group field tour methode by Brain Symphoni Technique Investigate how the advantages of implementation. To get the goal the reseacher used Quasi experiment by giving pre test and post test to two different classes as experiment and control class. In experiment class is given the reatment but control class is not. Based on that fact, the problems as follow (1) Is there any difference between creative student used group field tour methode by Brain Symphony technique and not? (2) Is the usage group field tour methode significant by Brain Symphoni thechnique in Creative Literature Writing. The technique is using Quasi experiment methode. Student used this methode is increasing the competence in short story. It showed by pre test and post test comparasion. In post test the score is significant comparated to control class. The control class is increasing too but it is not as big as experiment class. Key word: group field tour, literature learning.